Chemodynamical modelling of the Milky Way. Issue 8 (30th September 2016) - Binney, J.; Sanders, J. L.
Abstract: Chemodynamical models of our Galaxy that have analytic Extended Distribution Functions (EDFs) are likely to play a key role in extracting science from surveys in the era of Gaia.